Induction Therapy in Renal Transplant Recipients: A Review. (November 2014) - Laftavi, Mark Reza; Sharma, Rajeev; Feng, Lin; Said, Meriem; Pankewycz, Oleh
<x xml:space="preserve">Abstract</x> Transplant science has improved significantly over the last decade. Influenced by novel advancements, rejection rates and short-term graft losses diminished substantially. Induction therapy was shown to reduce rejection rates and improve short-term graft survival. In this article, we discuss the most commonly used induction agents and the choice of induction therapy in different renal transplant recipient subgroups. The medical literature as well as our own experience was used to prepare this review. At this time, induction therapy is commonly used in upwards of 80%, of renal transplant recipients. Depleting agents are the most frequently used agents and they account for more than 75% of all induction therapies in the United States. Currently, there is no consensus regarding the choice of induction therapy. The type of induction therapy is generally selected based on a comprehensive evaluation of the recipient and the donor's immunological risks, the risk of developing opportunistic infection and malignancy, recipient comorbidities, financial burden and the choice of maintenance immunosuppressive regimen.